Cancer incidence in a Swedish cohort with high exposure to perfluoroalkyl substances in drinking water - Li, Huiqi; Hammarstrand, Sofia; Midberg, Bo; Xu, Yiyi; Li, Ying; Olsson, Daniel S.; Fletcher, Tony; Jakobsson, Kristina; Andersson, Eva M. (Environmental research, 2022)
The use of firefighting foams at a military airport resulted in high levels of perfluorinated substances (PFAS) in the drinking water distributed to one-third of households in the Swedish municipality of Ronneby between the mid-1980s and the end of 2013. The Ronneby Register Cohort, a large cohort comprising all individuals (N = 60,507) who ever lived in the Ronneby municipality during the period of drinking water contamination, was linked to the Swedish Cancer Register 1985–2016. Individual exposure was classified based on comprehensive data on yearly residential address and water distribution. External analysis explored standardized cancer incidence ratios (SIR) for residents never, or ever, residing in the contaminated water district, compared with those residing in other towns in the same county as reference population. Cox models provided hazard ratios (HR) for different exposure groups within the cohort. 5,702 individuals with cancer were identified. SIR for overall cancer was 1.04 for men (95%CI 0.96–1.12) and 0.89 for women (95%CI 0.82–0.96) who ever lived in the contaminated drinking water area. Kidney cancer, which was reported with increased risk in C8 study, showed somewhat elevated HR in this study (HR 1.27; 95%CI 0.85–1.89). The HR was modestly elevated for bladder cancer (HR 1.32; 95%CI 1.01–1.72), and reduced for prostate cancer (HR 0.83; 95%CI 0.71–0.98). In subjects who ever lived in the contaminated water area during 2005–2013, when exposure was estimated to be highest, higher risks for kidney cancer (HR 1.84; 95%CI 1.00–3.37) but lower for prostate cancer (HR 0.76; 95%CI 0.59–0.98) were observed. Analysis of this large cohort exposed to high levels of PFAS, dominated by PFHxS and PFOS, revealed no evidence for an overall increased risk of cancer. A moderately increased risk of kidney cancer was observed, in accordance with previous findings after PFAS exposure dominated by PFOA. •One third of Ronneby residents were exposed to PFAS from firefighting foams via drinking water.•We included all individuals who had ever resided in Ronneby between 1985 and 2013.•The study population and study time period was fully covered by the Swedish Cancer Register.•We performed external and internal analyses, to obtain better estimate of cancer risk in relation to PFAS exposure.•No overall excess risk of cancer but modestly increased risk of kidney cancer in this population.